Immaterial Fordism: the paradox of game industry labour. (1st January 2007) - ,
Abstract : In different ways, Marxist autonomist, regulation school, and neoliberal theories all claim that work in the new economy is increasingly characterised by high levels of creativity, cooperation, and innovation, albeit accompanied by uncertainty and a relentless pace of work, introducing a new form of labour that differs fundamentally from past forms. This paper does not disagree with the proposition that capital is currently in the process of intensifying its search for more efficient value extraction. However, through a case study of lawsuits launched against the video game company Electronic Arts regarding its labour practices, it argues that the change in the nature of knowledge work and immaterial labour has been overstated by the adherents of these three schools and that what we are witnessing is not so much a replacement of traditional Fordist practices by post-Fordist ones as a new fusion of the two forms.